Akibat Hukum Bagi Partai Politik Jika Yang Tidak Melaksanakan Pertanggung Jawaban Keuangan Negara - Ahlan Ramadana; Rini Anggraini; Al-Khanif (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Starting from the focus, the problem of transparency in the use and management of political party funds is still a concrete problem at this time. Currently, many political parties are not yet disciplined in recording the receipt, management and expenditure of their political party funds. From the problems above, the first problem was formulated, what are the legal consequences for political parties if they do not carry out state financial accountability? Second, how will the legal consequences be reformulated for political parties that do not carry out accountability reports in accordance with Article 34 of Law No. 2 of 2011 concerning Political Parties? Based on the thoughts above, the author uses a type of normative juridical research which places law as a building system of norms, with a regulatory-legislative approach, conceptualization and comparison. Political party administrators should have a strategic plan to make the political party's budget more productive than before. This assessment of political party budget funds is considered unproductive or there is no progress from the political parties themselves in allocating their budgets, then. The policies contained in Law No. 2 of 2008 in conjunction with Law No. 2 of 2011 concerning political party budgets which are the basis for building facilities, infrastructure and education are considered by the public to be in vain and generally have the potential to be misused.